Tourism carrying capacity in the municipalities of Tolmin, Kobarid and Komen - Jurinčič, Igor (Acta geographica Slovenica, 2022)
The study of tourism carrying capacity in the municipalities of Tolmin, Kobarid and Komen has shown that the infrastructural and economic carrying capacity is the most problematic, as most indicator limits are already exceeded in the summer season. The most favourable is the spatial-ecological carrying capacity, where none of the studied indicator limits were exceeded. The results of the carrying capacity assessment for tourism in these municipalities should not be used as a tool to restrict tourism development, but rather as expert recommendations to promote more sustainable tourism development. Infrastructure identified as deficient cannot be improved immediately. Improvements require large financial investments that municipalities are not able to ensure quickly. We need a tourism development strategy that, in addition to all the necessary improvements, comprehensively addresses the problems that municipalities face from overtourism, especially during the high season.